Applied Big Data Driven Study on Shock Absorption and Tolerance Bands of Staple Food Commodities Price Volatility in East Java - Firman Sihol Parningotan; Avi Aviliani; Jonathan Herawan; Matthew Kartawinata (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2025)
This study investigates the day-to-day volatility dynamics of five staple food commodities in East Java which are Red Bird’s Eye Chili Pepper, Medium Rice, Bendera Powdered Milk, Free-Range Chicken Meat, and Commercial Chicken Eggs. By utilizing daily price data from January 1, 2021, to February 2, 2025, collected via big-data scraping of a government price monitoring website. A GARCH model with Student-t innovations is fitted to each return series, from which one-day 95% Value-at-Risk (VaR) thresholds are derived to establish an evidence-based "tolerance band" for policy intervention. The results show that Red Bird’s Eye Chili Pepper has the widest band, with an allowable daily drop of 2.5% and a rise of 10.14%, whereas Bendera Powdered Milk exhibits the narrowest range. All five series display extreme volatility persistence coefficients are near or above 1, but a critical finding is that the markets for Medium Rice and Free-Range Chicken Meat are not shock absorbent, with persistence values exceeding 1. This indicates that any market disruption has a permanent effect on their future volatility, pointing to deep structural inefficiencies. These empirically derived VaR-based guardrails provide a quantitative framework for timely market stabilization, while the persistence analysis highlights the need for long-term structural reforms, particularly for the rice and chicken sectors. Keywords: food price volatility; GARCH;  value-at-risk; big data. JEL: C54, Q11, Q1